Risk Factors Affecting The Case Of Diarrhea In Toddlers At UPTD Puskesmas Aek Kota Batu, In Na Ix-X Sub- District, North Labuhanbatu Regency In 2022 - Tivany Ovilla Muliadi (Sean Institute, 2022)
The condition when toddlers lose fluids and become dehydrated happens when they experience diarrhea. It is one of the leading causes of morbidity and mortality in toddlers, globally Poor hygiene makes diarrheal illnesses spread from person to person or through contaminated food or water. Diarrhea is responsible for 9% of toddler morbidity worldwide, and its prevalence is still high. This study is aiming to identify the risk factors that affect the case of diarrhea in toddlers. In the Na IX X subdistrict of the Labuhan Batu Utara regency. This analytical cross-sectional study employs 517 mothers with toddlers in NA IX- X, North Labuhan Batu Regency, who serves the study's population. In the end, 59 participants make up the sample of the study determined by using simple random sampling. Questionnaires are given to mothers of toddlers to gather the data. Univariate analysis, bivariate analysis with the Chi-Square test, and multivariate analysis with the logistic regression test are carried out to analyze the data. The findings indicate the correlation between diarrhea cases in children, knowledge, attitude, food hygiene, and accessibility to waste disposal facilities. It is discovered that knowledge (p=0.001; PR= 6.4; 95% CI 2.859- 82.466) is the dominant variable. This indicates that the case of diarrhea in toddlers is significantly influenced by the variable of knowledge. Additionally, it is found that toddlers of mothers with inadequate information are 6.4 times more likely to experience diarrhea, compared to mothers with better knowledge about this issue. It is advised that all parties, notably the community health center